2021
DOI: 10.7717/peerj.10868
|View full text |Cite
|
Sign up to set email alerts
|

Genome size versus geographic range size in birds

Abstract: Why do some species occur in small, restricted areas, while others are distributed globally? Environmental heterogeneity increases with area and so does the number of species. Hence, diverse biotic and abiotic conditions across large ranges may lead to specific adaptations that are often linked to a species’ genome size and chromosome number. Therefore, a positive association between genome size and geographic range is anticipated. Moreover, high cognitive ability in organisms would be favored by natural selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…The genome of birds is generally small, staying in the range from 0.91 Gb (blackchinned hummingbird, Archilochus alexandri) to 1.3 Gb (common ostrich, Struthio camelus) [52]. In addition to a generally smaller size, the bird genome is characterized by a lower number of repetitive elements [53,54], a low proportion of non-coding regions in general, and intensive evidence of gene loss [54].…”
Section: Avian and Peafowl Genomics And Genetics Avian And Peafowl Om...mentioning
confidence: 99%
“…The genome of birds is generally small, staying in the range from 0.91 Gb (blackchinned hummingbird, Archilochus alexandri) to 1.3 Gb (common ostrich, Struthio camelus) [52]. In addition to a generally smaller size, the bird genome is characterized by a lower number of repetitive elements [53,54], a low proportion of non-coding regions in general, and intensive evidence of gene loss [54].…”
Section: Avian and Peafowl Genomics And Genetics Avian And Peafowl Om...mentioning
confidence: 99%
“…[ 8 ] found that GS was indeed related to phenotypic plasticity in thermal sensitivity in several life-history traits across distinct Drosophila melanogaster genotypes. Second, in comparative studies, species with larger genomes have been found to have larger environmental and geographical distributions in bacteria [ 17 ], birds [ 18 ] and caddisflies [ 19 ], consistent with larger genomes being better able to produce viable phenotypes under a wider range of environments.…”
Section: Introductionmentioning
confidence: 99%